Cyclic voltammetry analysis of carbon based electrochemical capacitor in aqueous electrolytes - Raja Seman, Raja Noor Amalina; Munawar, Rose Farahiyan; Abd Razak, Jeefferie; Zulkapli, Nor Najihah; Bistamam, Mohd Shahril Amin; Talib, Elyas; Tunku Kudin, Tunku Ishak; Abdul Manaf, Nor Syafira; Mohd Abid, Mohd Asyadi Azam (Trans Tech Publications, 2015)
In this study, a mixture of activated carbon (AC) and graphene (G) was coated onto the stainless steel (SS) mesh to produce an electrode for the electrochemical capacitor (EC). Different materials, such as carbon nanotube (CNT) mixed with G, were also used in this experiment to compare the electrochemical properties of both electrodes. The electrochemical properties of the electrode were determined by using cyclic voltammetry (CV). The CV curves of the AC/G electrodes showed good capacitive behaviour, and the highest capacitance values obtained for AC/G and CNT/G electrodes in 1M H2SO4 at 1 mVs-1 were 13 Fg-1 and 4.34 Fg-1, respectively. Meanwhile, the highest capacitance values obtained in 6M KOH at 1 mVs-1 were 14 Fg-1 and 12.07 Fg-1 for AC/G and CNT/G electrodes, respectively.